Issues facing families of infants discharged after cardiac surgery: the perceptions of charity helpline staff. (30th March 2018) - Wray, Jo; Tregay, Jenifer; Bull, Catherine; Knowles, Rachel L.; Crowe, Sonya; Brown, Katherine
Abstract: Aim: To elicit the perceptions of helpline staff who talk to parents of children discharged after cardiac surgery in infancy about parents' key concerns. Methods: A qualitative study involving semistructured interviews with 10 staff at four heart charities. Interviews were recorded, transcribed and analysed using Framework analysis. Results: Staff identified the knowledge, communication and support needs of parents which they described in terms of the impact of patient and family factors, sources of support and systems. Staff perceptions of helplines, in terms of the function of a helpline and the roles of its staff, together with staff's personal views based on their experience of multiple encounters with many families, influenced how they viewed families' needs and responded to their requests. Conclusion: Helpline staff provided important, previously uncaptured evidence about the challenges faced by parents of children discharged after cardiac surgery in infancy. Staff have an important role in supporting communication, in terms of speaking to families about how to talk to professionals and talking to professionals directly to get or give information when parents are unable to do so. Capturing the perspective of helpline staff about communication issues has highlighted the need for interventions with professionals as well as parents.